2016
DOI: 10.1021/acs.langmuir.6b01143
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Origami and the Influence of Cholesterol on Lipid Packing

Abstract: ABSTRACT:The artificial phospholipid Pad-PC-Pad was analyzed in 2D (monolayers at the air/water interface) and 3D (aqueous lipid dispersions) systems. In the gel phase, the two leaflets of a Pad-PC-Pad bilayer interdigitate completely, and the hydrophobic bilayer region has a thickness comparable to the length of a single phospholipid acyl chain. This leads to a stiff membrane with no spontaneous curvature. Forced into a vesicular structure, Pad-PC-Pad has faceted geometry, and in its extreme form, tetrahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 40 publications
6
47
0
Order By: Relevance
“…For example, the group of Zumbühl synthesized modified diamidophospholipids, which self-assembled into interesting d-form vesicles or cuboid liposomes by using hydrogen bonding networks from well-designed lipids. [58][59][60][61] Block copolymers have the advantage of being adjustable and easily tunable to desired characteristics of the vesicles (Fig. 3e).…”
Section: (D) Chemical Versatilitymentioning
confidence: 99%
“…For example, the group of Zumbühl synthesized modified diamidophospholipids, which self-assembled into interesting d-form vesicles or cuboid liposomes by using hydrogen bonding networks from well-designed lipids. [58][59][60][61] Block copolymers have the advantage of being adjustable and easily tunable to desired characteristics of the vesicles (Fig. 3e).…”
Section: (D) Chemical Versatilitymentioning
confidence: 99%
“…6. The cholesterol is seemed to incorporate in a lipid bilayer membrane such as liposome, remove the membrane interdigitation, and induce a liquid-ordered phase [27,28]. It is suggested that a high amount of cholesterol orientates in the acyl chain of the C 12 -GLG-C 12 membrane more than liposomes due to the spacer of C 12 -GLG-C 12 consisting two glutamic acids and a lysine is larger than that of phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…With two times 0.7 nm for the headgroups, the hydrophobic layer is 1.8 nm thick. 12 An alltrans alkyl chain of 16 C-atoms has a length of 2.05 nm. 28 Thus, the alkyl chains in a non-interdigitated bilayer would have a tilt angle of 64°, which is rather unlikely.…”
Section: Cryo-transmission Electron Microscopy (Cryo-tem)mentioning
confidence: 99%